2021
DOI: 10.3390/en14196164
|View full text |Cite
|
Sign up to set email alerts
|

Home Bio-Waste Composting for the Circular Economy

Abstract: The consequence of the current economic development model is the generation of large amounts of waste and energy losses. One way to change this negative trend is a more rational use of raw materials reducing the amount of generated wastes. Biowaste, which may be divided into garden and kitchen waste, constitutes the main part of municipal waste. At the household level, it can be managed through composting—the most sustainable way of biowaste management. In this context, this paper aims to assess the economic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 59 publications
0
12
0
4
Order By: Relevance
“…Other studies showed the biodegradation in a home composting environment of fully green composites produced by reinforcing bio-based and biodegradable matrices with success (Pantaloni et al, 2020) and compostable diapers as a first step prior to full-scale composting (Colón et al, 2013). In conclusion, it is evident that the changes in the current household biodegradable waste management introduced by home composting generate positive economic and environmental effects, this strategy being in accordance with circular economy principles (Sulewski et al, 2021).…”
Section: Particular Situationsmentioning
confidence: 82%
“…Other studies showed the biodegradation in a home composting environment of fully green composites produced by reinforcing bio-based and biodegradable matrices with success (Pantaloni et al, 2020) and compostable diapers as a first step prior to full-scale composting (Colón et al, 2013). In conclusion, it is evident that the changes in the current household biodegradable waste management introduced by home composting generate positive economic and environmental effects, this strategy being in accordance with circular economy principles (Sulewski et al, 2021).…”
Section: Particular Situationsmentioning
confidence: 82%
“…This can help reduce unemployment and increase people's economic independence. According to Sulewski et al (2021), the management of household waste into compost has a positive economic and environmental impact. The problem is that the promotion of home-level composting requires active support from local governments, both in the financial dimension and by increasing the environmental awareness of residents.…”
Section: Waste Composting and Circular Economymentioning
confidence: 99%
“…Composting is the most sustainable way of waste management, where composting becomes an effort to use raw materials more rationally while reducing the amount of waste produced (Sulewski et al, 2021). Making maximum use of waste indirectly avoids resource depletion and improves the quality of life for the community (Hoa & Khanh, 2021) (Hoa & Khanh, 2021).…”
Section: Waste Composting and Circular Economymentioning
confidence: 99%
See 1 more Smart Citation
“…extensive sources of humus-forming organic matter and nutrients needed by plants while composting these resources into valuable and safe fertilisers restore the soil's value (Piwowar, 2013). In addition, it should be noted that the management of sewage sludge and waste from agri-food processing is part of Poland's environmental policy and the concept of circular economy, which has been a priority in European Union countries since 2015 (Sulewski et al, 2021). In addition, considering the current social and economic situation in Poland and other European Union countries, attention should be paid to the increasing prices of mineral fertilisers and their availability.…”
Section: Introductionmentioning
confidence: 99%